TUNING OF LOCAL MULTICOMPUTERS TO SPECIFIC TASKS - Boyakhchyan, I. E.; Shoukourian, S. K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
The problem of tuning of computer systems to specific tasks is considered. A review of existing tools that provide tuning on different levels for a specific class of computer systems named local area multicomputers is presented. A comparative analysis of considered tools is given according to their functional characteristics.